Mini-laparatomy radical cysto-prostatectomy for urinary bladder carcinoma (Journal of KIST Medical College, 2020)
Introduction: Open radical cysto-prostatectomy (RCP) is the gold standard for invasive urinary bladder cancer in male. Though minimal invasive technique like laparoscopic or robotic assisted surgery is gaining popularity for surgical management in developed countries, open mini laparotomy is equally effective with similar oncological outcome and morbidity result. Our study aims to evaluate the feasibility of Mini-laparotomy RCP with ileal conduit (IC) or neobladder.Methods: This is a descriptive cross-sectional study of 25 patients conducted from October 2016 to December 2019. Nineteen patients had muscle invasive urinary bladder cancer (MIBC), four had multifocal high grade non-muscle invasive bladder cancer (NMIBC) and two were BCG failure patients. Nineteen patients underwent RCP with IC and six with RCP and ileal Neobladder. We analyzed technical difficulty, operative time, blood loss, peri-operative complication for minilaparotomy RCP.Results: The mean age of patients was 63.2 years (46-81years). The mean operative time was 274 minute (180-420 minutes) with mean blood loss of 470 ml (300-2000 ml). Mean post-operative ileus was observed for 2.8 days (2-4 days). All patients stayed in the hospital for mean days of 12.84 (7 to 25 days). All patients were mobilized early with mean intensive care unit (ICU) stay of 2.52 days. Mean lymph node extraction was 17.6. Two patients died of renal failure and hyperosmolar diabetes mellitus.Conclusion: Minilaparatomy RCP is a feasible option in terms of early recovery with acceptable morbidity without compromising the oncological principles.